2011
DOI: 10.1002/asi.21660
|View full text |Cite
|
Sign up to set email alerts
|

Publication fees in open access publishing: Sources of funding and factors influencing choice of journal

Abstract: Open access (OA) journals distribute their content at no charge and use other means of funding the publication process. Publication fees or article-processing charges (APC)s have become the predominant means for funding professional OA publishing. We surveyed 1,038 authors who recently published articles in 74 OA journals that charge APCs stratified into seven discipline categories. Authors were asked about the source of funding for the APC, factors influencing their choice of a journal and past history publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
202
2
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 214 publications
(222 citation statements)
references
References 11 publications
12
202
2
6
Order By: Relevance
“…2 Authors have often had to patch together the funding needed to pay for an APC (both full OA and hybrid) from a number of sources, which could include allowable cost allocations in project funding, institutional dedicated APC funds, general overhead money, and even personal funds. 4 This has meant that many authors have been sensitive to the price level.…”
Section: Introductionmentioning
confidence: 99%
“…2 Authors have often had to patch together the funding needed to pay for an APC (both full OA and hybrid) from a number of sources, which could include allowable cost allocations in project funding, institutional dedicated APC funds, general overhead money, and even personal funds. 4 This has meant that many authors have been sensitive to the price level.…”
Section: Introductionmentioning
confidence: 99%
“…January 2013. Similar to the study of Solomon and Bjork, 32 we cannot estimate the percentage of waivers or discounts granted to authors but have assumed that waivers have been granted for only a small percentage of the articles published in OA journals that charge fees. We also found a small number of publishers who indicated that their journals charged fees, but we were unable to locate any indication of a fee in the instructions for authors or other documentation on the journal website.…”
Section: Methodsmentioning
confidence: 99%
“…On this last point, while open access avoids the monopolistic elements of closed subscriptions, funders may still want to introduce spending caps on publisher expenses, much as SCOAP3 uses in its contracts with publishers, as well as provide incentives to authors and publishers for fair and transparent pricing [4,20]. Introducing a form of centralized pricing will pose its own challenges, however, with much to be learned from the experience of the U.S.…”
Section: Bioonementioning
confidence: 99%